Design and synthesis of a novel series of histamine H3 receptor antagonists through a scaffold hopping strategy. Issue 3 (1st February 2015) - Gao, Zhongli; Hurst, William J.; Hall, Daniel; Hartung, Ryan; Reynolds, William; Kang, Jiesheng; Nagorny, Raisa; Hendrix, James A.; George, Pascal G.
Graphical abstract: Abstract: Lead compounds 5-fluoro-2-methyl- N -[2-methyl-4-(2-methyl-[1, 3′]bipyrrolidinyl-1′-yl)-phenyl]-benzamide (1 ), tetrahydro-pyran-4-carboxylic acid [((2 S, 3′ S )-2-methyl-[1, 3′]bipyrrolidinyl-1′-yl)-phenyl]-amide (2 ), and 3, 5-dimethyl-isoxazole-4-carboxylic acid [((2 S, 3′ S )-2-methyl-[1, 3′]bipyrrolidinyl-1′-yl)-phenyl]-amide (3 ) discovered in our laboratory, displayed high histamine H3 receptor (H3 R) affinity, good selectivity and weak human Ether-à-go-go-Related Gene (hERG) channel affinity with desirable overall physico-chemical and pharmacokinetic (PK) profiles. Herein, we describe the design and synthesis of a novel series of H3 R antagonists utilizing a scaffold hopping strategy. Further structure–activity relationship (SAR) studies of the series culminated in the identification of ((2 S, 3′ S )-2-methyl-[1, 3′]bipyrrolidinyl-1′-yl)-naphthalene-2-carboxylic acid (tetrahydro-pyran-4-yl)-amide (4c ) and -[4-((2 S, 3′ S )-2-methyl-[1, 3′]bipyrrolidinyl-1′-yl)-phenyl]- N -(tetrahydro-pyran-4-yl)-acetamide (4d ), which exhibited good H3 R affinity in vitro, good selectivity, and desirable PK properties. Compounds4c and4d were also assessed in cardiac safety experiments. In particular, the effects of the compounds on action potentials recorded from ventricular myocytes isolated from guinea pigs were used to screen compounds that not only displayed a low affinity towards hERG channel, but also had lower interference with other cardiac ion channels. Compound4c did not alter the major parameters in this model system at ⩽10 μM, and no significant induction of any major haemodynamic effect when intravenously administered at 3 mg/kg dose to anaesthetized mongrel dogs. Compound4c is a new promising lead as orally potent and selective H3 R antagonist belonging to a distinct structural class.